Mammalian olfactory receptors - Fleischer, Joerg; Breer, Heinz; Strotmann, Joerg (Frontiers in Cellular Neuroscience, 2009)
Perception of chemical stimuli from the environment is essential to most animals; accordingly, they are equipped with a complex olfactory system capable of receiving a nearly unlimited number of odorous substances and pheromones. This enormous task is accomplished by olfactory sensory neurons (OSNs) arranged in several chemosensory compartments in the nose. The sensitive and selective responsiveness of OSNs to odorous molecules and pheromones is based on distinct receptors in their chemosensory membrane; consequently, olfactory receptors play a key role for a reliable recognition and an accurate processing of chemosensory information. They are therefore considered as key elements for an understanding of the principles and mechanisms underlying the sense of smell. The repertoire of olfactory receptors in mammals encompasses hundreds of different receptor types which are highly diverse and expressed in distinct subcompartments of the nose. Accordingly, they are categorized into several receptor families, including odorant receptors (ORs), vomeronasal receptors (V1Rs and V2Rs), trace amine-associated receptors (TAARs), formyl peptide receptors (FPRs), and the membrane guanylyl cyclase GC-D. This large and complex receptor repertoire is the basis for the enormous chemosensory capacity of the olfactory system.